THE EFFECT OF WORK ENVIRONMENT AND INDIVIDUAL CHARACTERISTICS ON MEDICAL MEDICAL EMPLOYEE PERFORMANCE AT PT SARI TANI SUMATRA - Jonnathan Dingel; Mark G. Maffett (PT. Radja Intercontinental Publishing, 2023)
This study aims to determine how the influence of the work environment and individual characteristics on employee performance. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. 1) a ttable value of 2.048 is obtained. From this description it can be seen that tcount (5.613) > ttable (2.048), likewise with a significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the Work Environment Variable (X1) significant effect on Employee Performance Variable (Y). 2) a ttable value of 2.048 is obtained. From this description it can be seen that tcount (1.488) < ttable (2.048), and a significance value of 0.148 > 0.05, it can be concluded that the second hypothesis is rejected, meaning that the Individual Characteristics Variable (X2) has no significant effect on the Employee Performance Variable (Y). 3) the Ftable value is 3.35. From this description it can be seen that Fcount (15.768) > Ftable (3.35), and a significance value of 0.000 <0.05, it can be concluded that the fourth hypothesis is accepted, meaning that the Work Environment Variable (X1) , Individual Characteristics Variable (X2), has a significant simultaneous effect on Employee Performance Variables (Y).